Young khalaal dates (Phoenix dactylifera) effect on blood glucose in alloxan-induced wistar male rats - Desty Muzarofatus Sholikhah; Bambang Wirjatmadi; Merryana Adriani (Health Notions, 2018)
This study analyzed young dates (Phoenix dactylifera) effect on blood glucose in alloxan-induced male wistar rats. It used a completely randomized design with pre-post test and control group design. The research samples were 25 male white wistar rats that divided into 5 groups: (1) negative control group with no treatment (K1); positive control group with alloxan induction only (K2); treatment group 1 with alloxan induction and 0.25 g/day of young dates treatment (P1); treatment group 2 with alloxan induction and 0.5 g/day of young dates treatment (P2); and treatment group 3 with alloxan induction and 1 g/day of young dates treatment (P3). The result were tested by Kolmogorov-Smirnov normality test (p>0.05), Levene's homogeneity test (p>0.05), followed by General Multivariate Manova test by Wilks' Lambda, between-subject effect test, and LSD (p<0.05). The results indicated that young dates could effectively reduced the blood glucose levels (p = 0.000). The fasting blood glucose level in positive control group (K2) was different from negative control group (K1, p = 0.000) and all treatment groups (P1, p = 0.000, P2, p = 0.000 and P3, p = 0.000). 0.25 g/day of young dates treatment could effectively reduced the fasting blood glucose level in alloxan-induced male wistar rats. Keywords: young dates, blood glucose levels, alloxan